2015
DOI: 10.1530/jme-15-0089
|View full text |Cite
|
Sign up to set email alerts
|

Leptin signal transduction underlies the differential metabolic response of LEW and WKY rats to cafeteria diet

Abstract: Although the effect of genetic background on obesity-related phenotypes is well established, the main objective of this study is to determine the phenotypic responses to cafeteria diet (CAF) of two genetically distinct inbred rat strains and give insight into the molecular mechanisms that might be underlying. Lewis (LEW) and Wistar-Kyoto (WKY) rats were fed with either a standard or a CAF diet. The effects of the diet and the strain in the body weight gain, food intake, respiratory quotient, biochemical parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…1. Experimental design used to study the role of inbred rat models in nutritional genomics. The phenotypic response (described previously in Martínez-Micaelo et al, 2016) shows a differential susceptibility of LEW and WKY rats to the CAF diet. Here, we studied the differential modulation of the peripheral monocyte transcriptome of LEW and WKY rats by the CAF diet, as consequence of the prone and resistant responses of LEW and WKY rats, respectively, to the diet-induced obesity.…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…1. Experimental design used to study the role of inbred rat models in nutritional genomics. The phenotypic response (described previously in Martínez-Micaelo et al, 2016) shows a differential susceptibility of LEW and WKY rats to the CAF diet. Here, we studied the differential modulation of the peripheral monocyte transcriptome of LEW and WKY rats by the CAF diet, as consequence of the prone and resistant responses of LEW and WKY rats, respectively, to the diet-induced obesity.…”
Section: Resultsmentioning
confidence: 64%
“…Based on our previous results (Martínez-Micaelo et al, 2016), although both strains showed increased weight gain and adiposity in response to the CAF diet, plasma metabolic profiling evidenced contrasting phenotypic responses. Indeed, CAF diet challenge induced hyperglycaemia, hypertriglyceridaemia and higher levels of NEFAs in LEW rats, which was not the case for WKY rats.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations